Voice Biometric, A New Trend to Enhance Security (Trinity Journal of Management, IT & Media (TJMITM), 2015)
Security has always been a primary concern whether be it home or of fice. With the advent of information technology security over the infor mation acquired takes a prime concern. Security breaches are prevailing  from technical to business field. Information technology has inundated  the business sector and education world and every possible area one  can think of. Consider the case of CERT-I n where, Hours ahead of its  planned protest against certain incidents of internet censorship in India  , hacker collective Anonymous attacked and brought down the website  run by Computer Emergency Response Team India (CERT-I n). Amongst  the most disastrous information leakage breach was the hacking of data  for 1.5 million Master & VISA card users. VISA & MASTER card alerts  banks about the security breach at Global Payments. The alert clearly  stated that full Track 1 & Track 2 information was taken and could have  been abused for counterfeit new cards. This information had been com promised from a period of January 21,2012 to February 25,2012. Yet  it was not the company who disclosed the security breach, the security  blogger Brian Krebs in security reported the event on 30,March,2012,  This pattern is common for all security breaches as the conclusion who  are impacted are the last ones to know about it. These threats to business  need a stronger mechanism of security to counter them. Biometrics has  offered new venues to resolve these issues.Biometrics refers to the physiological or behavioural characteristics  of a person to authenticate his/her identity. This Biometrics is the most  prominent and promising technique used for authenticating a person’s  identity. Voice Biometrics, Finger printing, facial Recognition area few  biometrics that are used for security purposes. This paper majorly cover Voice Biometrics. voice biometrics uses the pitch, tone, and rhythm  of speech. Background noise, illness, age, and differences in telephones  and microphones can cause problems with voice identification and au thorization.[Paper: exploration - voice -biometrics_1436] This is mostly  used by Banks and Call Centres to authenticate there users. A telephone  or microphone is required to proved your identity. Voice Biometrics is  mostly adopted by the customers as they find it as a normal telephonic  conversation. Remotely any customer from any location can login or use  his/her ID. Each person has a unique voice and that can be easily stored in form of  bits. So, this provide a better option for the developer or programmers to  authenticate their software, databases etc using Voice Biometrics. Num ber of methods are used to apply these Biometrics. As a first step the new  user has to record his/her speech by calling a telephone collection script.  Once there is an existent recording the user is allowed to invoke an en rolment form and specify personal data, such as passwords and answers  to questions on various topics, as suggested by the server. The answers  can be selections from predetermined value lists, e.g. selected cities or  colours, or user’s own new keywords. It is also possible to add new ques tions within the existent topics or dynamically generate these based on  contexts or history of previous transactions or other events.
Keywords: Voice Biometric; CERT-I; Master & VISA; million Master & VISA; MASTER card